Zoxamide accumulation and retention evaluation after nanosuspension technology application in tomato plant. Issue 7 (21st April 2021) - Corrias, Francesco; Melis, Anna; Atzei, Alessandro; Marceddu, Salvatore; Dedola, Fabrizio; Sirigu, Antonella; Pireddu, Rosa; Lai, Francesco; Angioni, Alberto
Abstract: BACKGROUND: Low water solubility of pesticide requires formulations with high levels of stabilizers and organic solvents. Moreover, only 0.1% of the applied pesticides formulation reaches the target, while 99.9% spreads in the surrounding environment. Therefore, there is the need for more efficient and environmentally sustainable alternatives. RESULTS: Zoxamide (ZO) nanosuspension was prepared through a media milling technique by using the stabilizer polysorbate 80. The thin and acicular crystals obtained, showed particle size of 227 nm, polydispersion index of 0.247 and zeta potential of −28 mV. Dimensional data and morphology of ZO nanocrystals alone, on tomato leaves and berries, were confirmed by scanning electron microscopy. The reduction in size for ZO crystals obtained after the milling process increased pesticide water solubility till 39.6 mg L −1, about 1.6 the solubility obtained with a conventional commercial formulation. Field and dip contamination trials performed on tomato plants showed the nanosuspension's ability to increase ZO deposition and accumulation versus a coarse ZO suspension and commercial formulation, respectively. CONCLUSIONS: The nanoformulation proposed, resulted in low cost and was easy to make. Moreover, the organic solvent‐free composition together with a low surfactant addition assured a minor environmental impact. Finally, the increased retention and deposition of the fungicide can reduce the amounts of ZO formulation applied to tomatoes. © 2021 Society of Chemical Industry. Abstract : New water‐based eco‐friendly zoxamide nanocrystal formulations were prepared and fully characterized. Its ability to release pesticide residue in tomato plants (berries and leaves) was evaluated and compared with a zoxamide commercial formulation. © 2021 Society of Chemical Industry.